Optimal allocation of 30 GW offshore wind power in the Norwegian economic zone - S. Hølleland; G. D. Berentsen; H. Otneim; I. M. Solbrekke (Wind Energy Science)
The Norwegian Government aims to install offshore wind power with a total capacity of 30 GW by 2040, and the Norwegian Water Resources and Energy Directorate has suggested 20 candidate regions. We show that the potential for reducing overall power production variance across these regions is high using modern portfolio theory and the hourly and spatially rich reanalysis NORA3 Wind Power data set (NORA3-WP). The geographical diversification effect is demonstrated under various relevant scenarios, including a sequential build-out scenario with a fully connected Norwegian power grid assumption. By considering 20 alternative regions selected using a recently developed suitability score, we further illustrate that the diversification effect is robust to location changes.